BEYOND FUN: THE GAME AS A HUMAN RELATIONS TOOL IN THE EDUCATIONAL CONTEXT - dos Santos Oliveira, Valdineli; de Oliveira Azevedo Silva, Juliana; Cristiane Florencio dos Santos, Márcia; Maria da Silva Siqueira, Josivânia (Revista Gênero e Interdisciplinaridade, 2023)
“Games have the potential to stimulate human improvement, the playful environment is appealing, and it can be incorporated into the educational context. The aim of the study was to highlight how games can impact social interaction within a school structure. In order to achieve this, it was necessary to: a) identify how games can be used as an educational tool; b) explain how the educational environment can become more attractive when games are present, aiming to understand the mechanisms through which the use of games can positively affect students’ motivation and the quality of the learning experience; c) demonstrate how the integration of elements from an ‘imaginary world’ can contribute to transforming the school environment into a more pleasant and welcoming space for students. The study utilized a qualitative approach, and the data collection instrument employed was Document Analysis. Through the compilation of various documents, followed by an in-depth analysis, it was possible to realize that games should be present within the educational environment, constantly striving to make this environment increasingly appealing to students. Simultaneously, teachers will have an additional ally in the teaching and learning process. Additionally, as students learn while having fun, they will also be exposed to numerous conflicting experiences, which will further strengthen the development of their identity.”